2018
DOI: 10.1016/j.ymthe.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential but Complementary HIF1α and HIF2α Transcriptional Regulation

Abstract: Effective vascular regeneration could provide therapeutic benefit for multiple pathologies, especially in chronic peripheral artery disease (PAD) and myocardial ischemia. The hypoxia inducible factors (HIFs) mediate the cellular transcriptional response to hypoxia and regulate multiple processes that are required for angiogenesis to ultimately restore perfusion and oxygen supply. In endothelial cells, both HIF1α and HIF2α are known to contribute to this role; however, the extent and individual roles of each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 44 publications
(51 reference statements)
1
131
0
Order By: Relevance
“…In the canonical hypoxia‐mediated transcription pathway, HIF‐1α/2α‐HIF‐1β heterodimer binds to the HRE characterized by a conserved RCGTG DNA motif . HIF‐1α/2α have been implicated in transcriptionally regulating themselves in a positive feedback manner, and canonical target genes associated with the promoter histone modification, along with the cofactor involvement, may represent additional layers of regulation . Indeed, our data revealed that ectopically overexpressed SphK2 led enhanced promoter occupancy of HIF‐1α protein on the HIF‐2α promoter, and conversely, knockdown of SphK2 led reduced hypoxia‐mediated HIF‐1α binding of the HIF‐2α promoter in breast cancer cells (Figure ).…”
Section: Discussionmentioning
confidence: 74%
“…In the canonical hypoxia‐mediated transcription pathway, HIF‐1α/2α‐HIF‐1β heterodimer binds to the HRE characterized by a conserved RCGTG DNA motif . HIF‐1α/2α have been implicated in transcriptionally regulating themselves in a positive feedback manner, and canonical target genes associated with the promoter histone modification, along with the cofactor involvement, may represent additional layers of regulation . Indeed, our data revealed that ectopically overexpressed SphK2 led enhanced promoter occupancy of HIF‐1α protein on the HIF‐2α promoter, and conversely, knockdown of SphK2 led reduced hypoxia‐mediated HIF‐1α binding of the HIF‐2α promoter in breast cancer cells (Figure ).…”
Section: Discussionmentioning
confidence: 74%
“…Extensive transcriptional analysis in endothelial cells revealed that HIF-1␣ and HIF-2␣ regulated 701 and 1,454 genes, respectively. HIF-1␣ transcription involved primarily metabolic reprogramming, whereas HIF-2␣ appeared to regulate angiogenic signaling and extracellular matrix remodeling (65). In another study, vGPCR was found to be a novel target of HIF-1␣ and one of the main viral angiogenic factors regulating the metabolic reprogramming of KSHV (21).…”
Section: Discussionmentioning
confidence: 97%
“…Myeloid cells have an active role in that process, acting as cellular chaperones to promote endothelial tip cell fusion during vessel formation and producing proangiogenic factors [20,21]. HIF2α modulates HIF1α-driven proangiogenic responses by expressing sFlt1, stabilizing proliferating vessels, and promoting healthy revascularization [22]; HIF1 and HIF2 bind to different HREs in gene promoters, both being required for maximal transcriptional activity [23].…”
Section: Discussionmentioning
confidence: 99%